Recovery of actinides from actinide-aluminium alloys by chlorination: Part III - Chlorination with HCl(g) - Meier, Roland; Souček, Pavel; Walter, Olaf; Malmbeck, Rikard; Rodrigues, Alcide; Glatz, Jean-Paul; Fanghänel, Thomas (Journal of nuclear materials, 2018)
Two steps of a pyrochemical route for the recovery of actinides from spent metallic nuclear fuel are being investigated at JRC-Karlsruhe. The first step consists in electrorefining the fuel in molten salt medium implying aluminium cathodes. The second step is a chlorination process for the separation of actinides (An) from An-Al alloys formed on the cathodes. The chlorination process, in turn, consists of three steps; the distillation of adhered salt (1), the chlorination of An-Al by HCl/Cl2 under formation of AlCl3 and An chlorides (2), and the subsequent sublimation of AlCl3 (3). In the present work UAl2, UAl3, NpAl2, and PuAl2 were chlorinated with HCl(g) in a temperature range between 300 and 400 °C forming UCl4, NpCl4 or PuCl3 as the major An containing phases, respectively. Thermodynamic calculations were carried out to support the experimental work. The results showed a high chlorination efficiency for all used starting materials and indicated that the sublimation step may not be necessary when using HCl(g).